Review of underbalanced drilling techniques highlighting the advancement of foamed drilling fluids - Jawad Al-Darweesh; Murtada Saleh Aljawad; Mustafa Al-Ramadan; Salaheldin Elkatatny; Mohamed Mahmoud; Shirish Patil (Journal of Petroleum Exploration and Production Technology, 2022)
Abstract Overbalanced drilling is the most common drilling technique; nevertheless, it has several disadvantages such as formation damage, mud losses, and stuck pipes; challenges that are common in high permeability zones and highly fractured formations. To overcome those issues, the underbalanced drilling method could be implemented. The underbalanced drilling (UBD) technique is widely utilized in hard, under pressure, depleted, and fractured/vuggy formations. Low-density drilling fluids are usually used in UBD operations and could be categorized into a gas (i.e., air, nitrogen, and natural gas) or two-phase (i.e., mist and foam). Although foamed fluid attracted attention in enhanced oil recovery and hydraulic fracturing operations, it is ideal for UBD operations due to its low density and efficient transport capacity. This paper highlights the applications, limitations, advantages, and disadvantages of UBD operations. It also discusses the drilling foam chemistry, structure, characterization, and rheological properties. Finally, this paper highlights a few successful UBD operations utilizing foamed drilling fluids worldwide.